2015
DOI: 10.1016/j.neuroimage.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying interindividual variability and asymmetry of face-selective regions: A probabilistic functional atlas

Abstract: Face-selective regions (FSRs) are among the most widely studied functional regions in the human brain. However, individual variability of the FSRs has not been well quantified. Here we use functional magnetic resonance imaging (fMRI) to localize the FSRs and quantify their spatial and functional variabilities in 202 healthy adults. The occipital face area (OFA), posterior and anterior fusiform face areas (pFFA and aFFA), posterior continuation of the superior temporal sulcus (pcSTS), and posterior and anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 100 publications
12
119
2
Order By: Relevance
“…In line with evidence from these lesion studies, here, the second largest face-selective responses were found in the right IOG and antFG, two regions in which highly face-selective responses were also clustered. The right IOG corresponds to the cortical territory where the OFA is typically located (16,17,51), so that our observations again validate the findings of neuroimaging studies of face perception. The right antFG is part of the ventral ATL, whose role in face perception is currently the focus of intense research (ref.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with evidence from these lesion studies, here, the second largest face-selective responses were found in the right IOG and antFG, two regions in which highly face-selective responses were also clustered. The right IOG corresponds to the cortical territory where the OFA is typically located (16,17,51), so that our observations again validate the findings of neuroimaging studies of face perception. The right antFG is part of the ventral ATL, whose role in face perception is currently the focus of intense research (ref.…”
Section: Discussionsupporting
confidence: 86%
“…Collectively, these studies have reported larger brain responses to face images than other visual objects in clusters, patches, or functional regions of a few cubic millimeters within the human VOTC (e.g., refs. [10][11][12][13][14][15][16]. The clusters consistently reported across studies are localized in the lateral part of the middle/posterior fusiform gyrus [fusiform face area (FFA)] (12) and in the lateral part of the inferior occipital gyrus [occipital face area (OFA)] (17), as well as in the posterior superior temporal sulcus, a region that may be involved in more general and dynamic social communication functions (18).…”
mentioning
confidence: 99%
“…First, it is unlikely that inputs from left IOG-faces support the stability of right pFus-faces because we were unable to identify IOG-faces in the left hemisphere in any session (Fig. 6A) and left IOG-faces is also not always detected in typical individuals (Zhen et al, 2015). Second, face selectivity in the left hemisphere (Fig.…”
Section: The Cortical Layout Of the Face Network Is Stable After Resementioning
confidence: 88%
“…right hemisphere dominance (Sergent et al, 1992;Puce et al, 1995;Haxby et al, 2000;Fox et al, 2008;Rossion, 2008;Pitcher et al, 2011a;Zhen et al, 2013;Duchaine and Yovel, 2015). A subset of these regions composes the "core" face network (Haxby et al, 2000): the inferior occipital gyrus/occipital face area (IOG-faces/ OFA) (Gauthier et al, 2000;Weiner and Grill-Spector, 2010), the fusiform gyrus (FG)/fusiform face area (FFA) (Kanwisher et al, 1997), which can be divided into separate regions on the posterior and mid-fusiform gyrus (Pinsk et al, 2009;Weiner and GrillSpector, 2010), and regions along the superior temporal sulcus (STS) (Puce et al, 1998;Pinsk et al, 2009;Pitcher et al, 2011b).…”
Section: Significance Statementmentioning
confidence: 99%
“…No participant was excluded due to excessive head motion (2 mm in translation or 2 degree in rotation from the first volume in any axis) or visually detected registration errors (Zhen et al 2015;Kong et al 2016b). Most of these participants (N = 167; 104 females; mean age = 20.2 years, SD = 0.90 years) completed three behavioral assessments, including a standard questionnaire on spatial navigation performance in daily life, a computer test on small-scale spatial ability, and a Raven task for general ability (see below).…”
Section: Participantsmentioning
confidence: 99%